Determinan Financial Distress pada Perusahaan Transportasi dan Logistik - Sanjaya, Riandana Aditya; M. Helmi, Syarif (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
The transportation and logistics industry is one of the sectors that has been significantly affected by global economic pressures, especially during the post-pandemic recovery period. This study aims to examine the influence of profitability, liquidity, leverage, sales growth, and firm size on financial distress in transportation and logistics companies listed on the Indonesia Stock Exchange during the period 2021–2024. The research employs a quantitative approach using multiple linear regression analysis, with sample selection carried out through purposive sampling based on the availability of financial statements over the observation period. This study adopts a signaling theory perspective to understand how internal financial indicators are used by management to communicate the firm’s financial condition, especially in the context of potential financial distress. The study concludes that financial distress is closely related to the quality of financial signaling presented by firms. Future research is recommended to consider qualitative dimensions and industry-specific challenges to improve the depth of financial distress analysis.